A Decision-Makers Guide to Public Private Partnerships in Airports - Ricover, Andy.; Delmon, Jeffrey (London : Routledge, 2019)
Airport development is critical to economic growth and poverty reduction.This book will help decision-makers assess whether Public Private Partnerships (PPP) might be aviable option to meet theirairport development requirements. It walks the reader through the airport PPP process, from early preparation to bringing the project to market and managing the project during implementation. The book will help eradicate misconceptions about the role of the private sector in airport infrastructure. A Decision-Makers Guide to Public Private Partnerships in Airports provides an essential guide for those in a position to make decisions linked to airport development, to their advisers, their staff and also to students wishing to understand airport PPP.
4.2 Associated infrastructure4.3 Traffic forecasting; 4.4 Master planning; 4.5 Consultation; 5 Air transport regulation; 5.1 The International Civil Aviation Organization (ICAO); 5.1.1 ICAO objectives; 5.1.2 Airport development and planning; 5.1.3 ICAO compliance; 5.2 International Air Transport Association (IATA); 5.2.1 Services; 5.2.2 Airport Development Reference Manual (ADRM); 5.2.3 IATA's enhancement and financing services (E&F); 5.3 Market access and air service agreements; 5.3.1 Bilateral air service agreements; Liberalisation; 5.3.2 Multilateral air service agreements (MASAs)
Description based upon print version of record.
Multilateral Agreement on the Liberalization of International Air Transportation (MALIAT)
OCLC-licensed vendor bibliographic record.
Keywords: ARCHITECTURE / Project Management; BUSINESS & ECONOMICS / Infrastructure; BUSINESS & ECONOMICS / Project Management; Airports -- Economic aspects; Public-private sector cooperation